OPTIMAL COMBINATION OF TOLUENE AND CLOVE OIL (Syizigium aromaticum) IN THE PROCESS OF CLEARING THE PERMANENT PREPARATION PEDICULUS HUMANUS CAPITIS - Ihsan, Bagus Muhammad; Liesvia, Vira; Armal, Hadits Lissentiya; Supriyanto, Supriyanto; Hanif, Muhammad Ifham (Media Penelitian dan Pengembangan Kesehatan, 2024)
Clearing is a vital process in microscopy, aimed at enhancing the transparency of tissue preparations for clearer observation of insect structures. Despite its effectiveness, Toluene poses safety concerns due to its explosive nature. Therefore, clove oil (Syzygium aromaticum) has been explored as a safer alternative. This study evaluates the quality of permanent preparations of Pediculus humanus capitis using both toluene and clove oil. Comparative tests were conducted, treating adult head lice specimens with each solvent for three repetitions. Permanent preparations were assessed for clarity, color quality, and morphological integrity. Results indicate a significant difference in quality between the two methods. Toluene yielded mainly poor-quality preparations, while clove oil resulted in a higher proportion of preparations of good quality. The Mann-Whitney test confirmed the significance of this difference (p = 0.002). This study highlights the efficacy of clove oil as a safer alternative to toluene in the clearing process, contributing to entomological practices and chemical safety.